2017
DOI: 10.1016/j.pmedr.2016.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of self-sampling in promoting participation to cervical cancer screening also in subsequent round

Abstract: Offering self-sampling devices improves participation of under-screened women. We evaluated participation in routine screening following the self-sampling intervention in two organized population-based screening programmes located in North-East Italy.Data on participation at 3-years-interval after a randomized clinical trial assessing the response to two strategies offering self-samplers (sent at home or offered free at local pharmacy) with a control action (sending reminders for a cervical specimen taken at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 12 publications
2
10
0
1
Order By: Relevance
“…The results of the current study indicate that higher self-efficacy was observed within participants who were enlightened about cervical cancer screening. This result is in line with the results of an interventional study performed by Del Mistro et al where the level of self-efficacy within the interventional arm increased significantly in comparison to the control arm ( 56 ). Women with improved self-efficacy are more likely to engage in appropriate health-related behaviours because these class of women might have their knowledge status being influenced due to their exposure to some information.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the current study indicate that higher self-efficacy was observed within participants who were enlightened about cervical cancer screening. This result is in line with the results of an interventional study performed by Del Mistro et al where the level of self-efficacy within the interventional arm increased significantly in comparison to the control arm ( 56 ). Women with improved self-efficacy are more likely to engage in appropriate health-related behaviours because these class of women might have their knowledge status being influenced due to their exposure to some information.…”
Section: Discussionsupporting
confidence: 91%
“…The findings of the present study suggest that women who were educated on cervical cancer and screening had higher self-efficacy. This finding is consistent with the findings of an intervention study conducted in Turkey in which levels of self-efficacy greatly improved in the intervention group compared to the control group [28]. Women with increased self-efficacy may have a higher tendency of engaging in health appropriate behaviours, since they may have been exposed to some information that may have influenced their knowledge status.…”
Section: Discussionsupporting
confidence: 89%
“…Given that cervical cancer screening is recommended at relatively infrequent intervals, often up to 5 years, it is understandable that studies generally did not assess this longer term outcome. One follow-up study to an included RCT found that, on regular invitation to subsequent clinic-based cervical cancer screening 3 years after invitation to an HPV self-sampling trial, there was no statistically significant difference in participation rate (approximately 30% in all arms) comparing those randomised to HPV self-sampling with HPV testing in clinic, whether prior self-sampling was conducted at home (RR: 1.05, 95% CI 0.90 to 1.22) or at a pharmacy (RR: 0.96, 95% CI 0.83 to 1.22) 56. However, although the initial RCT compared self-sampling (sent kit home or offered free at local pharmacy) with standard population-based screening (sent reminder for cervical specimen taken at clinic), all women at the 3-year follow-up timepoint were reinvited for clinic-based HPV screening.…”
Section: Discussionmentioning
confidence: 94%